2019
DOI: 10.1029/2019jb017603
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Topography Development North of Iceland from Subaerial Exposure of the Igneous Logi Ridge, NE Atlantic

Abstract: The Logi Ridge, located north of the West Jan Mayen Fracture Zone, is E-W oriented and 140-150 km long. The seafloor surrounding the Logi Ridge is ∼0.65 km shallower than the conjugate seafloor east of the Mohn's Ridge, attributed to asymmetry in the regional NE Atlantic dynamic uplift. Eight reflection seismic lines across the Logi Ridge constrain its development. Both the western and eastern parts have flat tops, indicating erosion at sea level. Three different basement types surrounding the Logi Ridge are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(27 citation statements)
references
References 67 publications
(137 reference statements)
0
27
0
Order By: Relevance
“…The magma generation rate depends on the duration of the Logi Ridge formation. If building starts at the Eocene/Oligocene boundary at about 35 Ma and is over by the Middle Miocene at around 15 Ma (Tan et al., 2019), the maximum duration is 20 Ma. If the magma generation was evenly distributed over this time interval, then the generation rate becomes approximately 0.02–0.04 m 3 /s.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The magma generation rate depends on the duration of the Logi Ridge formation. If building starts at the Eocene/Oligocene boundary at about 35 Ma and is over by the Middle Miocene at around 15 Ma (Tan et al., 2019), the maximum duration is 20 Ma. If the magma generation was evenly distributed over this time interval, then the generation rate becomes approximately 0.02–0.04 m 3 /s.…”
Section: Resultsmentioning
confidence: 99%
“…Traill Ø is located at the westernmost end of the TIC (Figure 2), where syenitic intrusions exposed onshore are dated to 10.1029/2021JB023891 4 of 24 34-36 Ma, coeval with the rifting of the JMMC (Noble et al, 1988;Price et al, 1997) (Figure 1). Tan et al (2019) found that the onset of formation of the Logi Ridge also started in the Oligocene, and that its formation correlates with a regional dynamic topography rise expected to come from the increasing Iceland Plume influence in the asthenosphere.…”
Section: Jmmc Breakup-related Magmatismmentioning
confidence: 89%
See 3 more Smart Citations